ISAIAH BERLIN AS A PHILOSOPHER AND A TEACHER - Olga L. Granovskaya (Высшее образование в России, 2016)
The purpose of the article is to show the type of a teacher of a Socratic type on the example ofa creative work of Isaiah Berlin. The author provides historical and philosophical reconstruction of Berlin’s intellectual heritage, which has revealed fundamental philosophical premises of the thinker’s educational concept. The author reveals main characteristics ofBerlin’s style of thinking (aesthetic richness, aphoristic nature, integrity and synergism), and concludes that Isaiah Berlin was a philosopher and a teacher of the Socratic type, he entered into a dialogue with his disciples and followers, helping them to make their own judgments about the subject of conversation. His understanding of the negative and positive conceptions of liberty has become canonical for the modern liberal thought, and his idea of value pluralism has become its basic assumption and its main difficulty.